Interplay of Vitamin D, Erythropoiesis, and the Renin-Angiotensin System. (27th April 2015) - Santoro, Domenico; Caccamo, Daniela; Lucisano, Silvia; Buemi, Michele; Sebekova, Katerina; Teta, Daniel; De Nicola, Luca
Abstract : For many years deficiency of vitamin D was merely identified and assimilated to the presence of bone rickets. It is now clear that suboptimal vitamin D status may be correlated with several disorders and that the expression of 1- α -hydroxylase in tissues other than the kidney is widespread and of clinical relevance. Recently, evidence has been collected to suggest that, beyond the traditional involvement in mineral metabolism, vitamin D may interact with other kidney hormones such as renin and erythropoietin. This interaction would be responsible for some of the systemic and renal effects evoked for the therapy with vitamin D. The administration of analogues of vitamin D has been associated with an improvement of anaemia and reduction in ESA requirements. Moreover, vitamin D deficiency could contribute to an inappropriately activated or unsuppressed RAS, as a mechanism for progression of CKD and/or cardiovascular disease. Experimental data on the anti-RAS and anti-inflammatory effects treatment with active vitamin D analogues suggest a therapeutic option particularly in proteinuric CKD patients. This option should be considered for those subjects that are intolerant to anti-RAS agents or, as add-on therapy, in those already treated with anti-RAS but not reaching the safe threshold level of proteinuria.